Напрямки посилення конкурентної позиції фірми в Інтернет - Нечай, Ангеліна Андріївна (Тернопіль, ЗУНУ, 2025)
У роботі систематизовано теоретичні засади формулювання конкурентної позиції фірми в цифровому середовищі та визначено роль інструментів інтернетмаркетингу в її забезпеченні, проаналізовано маркетингову активність digitalагенції Koala Masters та оцінено стратегію її конкурентного позиціонування в мережі Інтернет, розроблено комплекс заходів для посилення конкурентних позицій фірми та обґрунтовано їхню очікувану ефективність. The thesis systematizes the theoretical foundations for establishing a company’s competitive position in the digital environment and defines the role of internet marketing tools in securing it. An analysis of the marketing activity of the digital agency Koala Masters was conducted, and its competitive positioning strategy on the Internet was evaluated. A set of measures to strengthen the company’s competitive position was developed, and their expected effectiveness was substantiated.
Directions for strengthening the company’s competitive position online